Spring migration of European teals Anas crecca wintering in Italy - GIUNCHI, DIMITRI; BALDACCINI, NATALE EMILIO; LUSCHI, PAOLO; VANNI, LORENZO; Lenzoni A.; Sorrenti M. (University of Extremadura, 2015)
Tracking data on migratory movements of European ducks are relatively scarce and available information mainly belong to largest species. In 2013 we started a project aimed at collecting data on the ecology of migration of some species of dabbling ducks wintering in Italy by means of satellite tracking (AnaSat Project). Up to now we tagged 25 female European teals Anas crecca, the smallest duck in Europe and one of the most abundant. Teals were caught in three different sites in Central and Northern Italy and then equipped with solar powered PTTs. Most tracked birds left their wintering areas by the end of February-beginning of March and then followed eastward routes, While some females ended their migration in central Europe, several teals flew thousands of kilometers, sometimes reaching the arctic circle in Russia, thus confirming previous evidences collected by means of ringing recoveries and stable isotopes analyses. At the very beginning of migration, these long-distance migrating individuals used staging areas mainly located in south-eastern Europe. On the whole, this is the first analysis at individual level regarding the timing of migration and routes of teals and thus represent an important contribution for the management of the species at European scale